Value of Groundwater: Case studies in Banaskantha - Kumar, M. Dinesh; Singhal, L.; Rath, P. (2004)
A study carried out in four villages in Banaskantha district of Gujarat estimated that 60 per cent of the net farm output generated through groundwater use in agriculture came from dairying. Tubewell irrigation supports three-quarters of the farming household income in these villages and, strangely, this share is larger for water buyers and farm labourers than for tubewell owners. This is despite the fact that tubewell irrigation costs have soared rapidly with depleting water tables. Despite the high costs and depleting water tables, irrigated areas have increased steadily, making livelihoods even more precariously dependent upon sustainable groundwater management.